Stakeholder consultations in national education policy (2020): a qualitative evaluation of consultations in India’s education policyscape - Sunil Valliyil, D (2022)

(untitled)
This qualitative study attempts to evaluate the consultative process of India's National Education Policy (2020). Using a systemic lens, it aims to realise two broad research objectives. Firstly, it attempts to normatively differentiate between consultation theory and practice. Secondly, it aspires to define 'good consultation' and provide a contextual and comprehensive framework for this purpose. The elite interviews of NEP's policy leaders and document analysis of critical consultation policy texts produced three central findings. Firstly, while there is a consensus on the process and outcome goals of consultations across the stakeholders, the evidence demonstrates that it is not systematically measured or understood. Secondly, the consultations only poorly address the puzzle of public involvement. There is little to no empirical evidence of ambitious participation or effective systems. Thirdly, the consultative process is substantially different in theory and implementation. This incongruence has its advantages and disadvantages and can be observed in aspects such as the use of native language, local level participation and the adoption of technology. The policy texts and interview transcriptions were analysed using a reflexive thematic and content analysis processes, respectively. This analysis was founded on a relativist philosophy and performed through a social constructivist approach. Two insights emerged from the study and have a potential role in improving future consultative practices. First, consultations are normatively valuable and possess a negative capability to reform the education policyscape. Second, although it is evident that the critique of consultations is too perfunctory, the study concludes that it is crucial to ground policy rhetoric on policy reality to avoid such misconceptions.